Về thành phần hóa học của rễ cây mật nhân (Eurycoma longifolia Jack.) - Thanh Tâm, Nguyễn Thị; Phương Thảo, Trần Thị; Lộc, Trần Văn; Thủy, Ngô Thị; Như, Nguyễn Duy; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
Phytochemical study of the water extract of the roots of Eurycoma longifolia Jack. led to the isolation of three alkaloids 9,10-dimethoxycanthin-6-one (4), 9-hydroxycanthin-6-O-β-D-glucopyranoside (5), β-carboline-1-propanoic acid (6), one coumarin isoscopoletin (1) and β-sitosterol (3) whereas from the ethanol/water extract of the roots of this plant, six compounds were isolated including one quassinoid eurycomanol (8), glucose (7), β-sitosterol (3), daucosterol (2) as well as alkaloids (5) and courmarin (1). Their structures were elucidated by the mass, NMR spectroscopy and comparison with published data. Compound (1) has been isolated for the first time from this plant. Keywords: Eurycoma longifolia Jack., alkaloids, quassinoid, eurycomanol, β-carboline-1-propanoic acid, 9,10-dimethoxycanthin-6-one, 9-hydroxycanthin-6-O-β-D-glucopyranoside